IMPACT OF ELECTRONIC WORD OF MOUTH ON CONSUMER PURCHASE INTENTION- INVESTIGATING THE RESTAURANT INDUSTRY OF PAKISTAN - Ashraf, Mariam (2022)
With rapid technological advancement and advent of many social media networks, consumers have been using websites for online reviews and discussion platforms to a great extent. These platforms are also considered an important medium of marketing for product and service advancement. These platforms enable the consumer to share their honest reviews about products, services and companies and increase the transparency and availability of information which affect brand sales as well. The research aims to study how electronic word of mouth on these platforms affect consumer purchase intention in the restaurant sector of Pakistan and what other factors play a role in mediating the relationship. The research used one independent variable Electronic Word of Mouth, four mediating variables Information Credibility, Information Quality, Information Adoption and Social relationships and studies their impact on dependent variable Consumer Purchase Intention. The study uses 5 hypothesis and gathers the data through a survey from 70 respondents. The data is analysed using AMOS and SPSS through Structural Equation Modelling and results of the study accept all hypothesis which shows that Electronic Word of Mouth positively impacts Consumer Purchase Intention and other variables which are Information Credibility, Information Quality, Information Adoption and Social relationships positively mediate the relationship between EWOM and Consumer Purchase Intention. The result of the study will be helpful for both consumer and brand managers of eateries who can improve their services based on the opinions given by people and responding to negative reviews by studying the factors which shape consumer buying decisions.